OP0045 ABATACEPT TREATMENT OF PATIENTS WITH EARLY ACTIVE PRIMARY SJÖGREN'S SYNDROME – A RANDOMIZED, DOUBLE-BLIND PLACEBO-CONTROLLED PHASE. (June 2019) - Spijkervet, Fred K.L.; Onno Teng, Y.K.; Arends, E.J.; ,; van Nimwegen, Jolien F.; van Zuiden, Greetje S.; Arends, Suzanne; Mossel, Esther; Wijnsma, Robin F.; Stel, Alja J.; Delli, Konstantina; Vegt, Bert van der; et al.
Abstract : Background: Effective systemic treatment is not yet available for primary Sjögren syndrome (pSS). Abatacept (CTLA-4-Ig) targets the CD80/CD86:CD28 co-stimulatory pathway required for full T-cell activation and T-cell dependent activation of B-cells. IV abatacept was shown to be safe, well tolerated, and to decrease disease activity in an open-label study of 15 pSS patients. 1 Objectives: To assess the efficacy and safety of subcutaneous (SC) abatacept vs. placebo in patients with early active pSS. Methods: The Abatacept Sjögren Active Patients phase III (ASAP-III) study is a monocenter, investigator-initiated, double-blind, placebo-controlled trial (NCT02067910 ). ASAP-III included 80 adult patients with biopsy-proven pSS, fulfilling the AECG and ACR/EULAR criteria, with a disease duration of ≤7 years and moderate to high EULAR Sjögren's syndrome disease activity score (ESSDAI ≥5). Patients were randomized in a 1:1 ratio to receive weekly SC abatacept (125 mg) or placebo for 24 weeks (figure 1). After the double-blind phase, all patients were treated with abatacept in a 24-week open label phase. Concomitant use of other DMARDs was not permitted, with the exception of a stable dose of prednisone (≤10mg). Rescue therapy with prednisone or cyclophosphamide was permitted after week 12. Participants visited our pSS tertiary referral center nine times, to be evaluated by a multidisciplinary team of rheumatologists, ophthalmologists, and oral and maxillofacial surgeons. The primary endpoint is ESSDAI at 24 weeks. Secondary outcomes over 24 and 48 weeks include clinical, patient reported, functional, histological, laboratory, ultrasound, and microbiome parameters, and the occurrence of (serious) adverse events and treatment discontinuation. Results: Baseline characteristics of participants are shown in table 1. Database lock for the blinded stage is planned in March 2019. Subsequently, the first intention-to-treat analyses will be performed, focusing on the ESSDAI and EULAR Sjögren Syndrome Patient Reported Index (ESSPRI), quality of life (EQ-5D), unstimulated and stimulated whole salivary flow (UWS, SWS), Schirmer test, Ocular Staining Score (OSS), serological parameters (RF, IgG), and safety parameters. Conclusion: The ASAP-III trial was designed to assess the clinical efficacy and safety of SC abatacept in pSS patients with short disease duration and active disease. The 24-week results will be available during the EULAR congress 2019. Reference: [1] Meiners, et al. Ann Rheum Dis2014;73:1393-6. Disclosure of Interests: Jolien F. van Nimwegen Speakers bureau: Bristol-Myers Squibb, Greetje S. van Zuiden Speakers bureau: Roche, Suzanne Arends Grant/research support from: Grant/research support from Pfizer, Esther Mossel: None declared, Robin F. Wijnsma: None declared, Alja J. Stel: None declared, Konstantina Delli: None declared, Bert van der Vegt: None declared, Erlin A. Haacke: None declared, Lisette Olie: None declared, Leonie I. Los: None declared, Janita Bulthuis-Kuiper: None declared, Gwenny M. Verstappen: None declared, Sarah A. Pringle: None declared, Fred K.L. Spijkervet: None declared, Frans G.M. Kroese Grant/research support from: Unrestricted grant from Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, Roche, Janssen-Cilag, Arjan Vissink: None declared, Hendrika Bootsma Grant/research support from: Unrestricted grants from Bristol-Myers Squibb and Roche, Consultant for: Roche, Bristol-Myers Squibb, Novartis, Medimmune, Union Chimique Belge, Speakers bureau: Bristol-Myers Squibb, Novartis